PROGNOSTIC VALUE OF 18F-FDG POSITRON EMISSION TOMOGRAPHY IN THE EARLY EVALUATION OF THE EFFICIENCY OF TREATMENT IN PATIENTS WITH NON-HODGKIN LYMPHOMAS - M. M. Khodzhibekova; L. A. Tyutin; N. A. Kostenikov; N. V. Il’in; Yu. N. Vinogradova (Вестник рентгенологии и радиологии, 2016)
Objective: to define the role of 18F-FDG positron emission tomography (PЕT) performed after 2–3 chemotherapy cycles in the prediction of disease prognosis and to identify a group of patients requiring more intensive treatment.Material and methods. Seventy-one patients with nonHodgkin lymphoma of different histological types were examined. PET was carried out at different stages of diagnosis and primary treatment in the patients.Results. The examinations made after 2–3 polychemotherapy (PCT) cycles indicated that 36 (50.7%) patients continued to have signs of metabolic activity of lymphoproliferative disease (a PET-positive group) and 35 (49.3%) patients were found to have no abnormal tracer accumulation foci (a PET-negative group). Twenty-nine (82.9%) patients from the PET-negative group continued to remain in complete remission throughout the follow-up (the median follow-up was 405 days). At late stages, 6 (17.1%) patients were identified to have abnormal tracer hyperfixation foci that were indicative of disease recurrence. Only 8 patients from the PET-positive group were observed to show a complete metabolic response to treatment at the end of first-line PCT. The metabolic activity of the disease was maintained in the remaining patients. The results of PET conducted at the late stages of the follow-up indicated that metabolically active tumor foci continued to be visualized in 20 (55.6%) patients and further treatment resulted in complete remission in 16 (44.4%) patients.Conclusion. PET findings could predict the further course of the disease and differentiate more intensive treatment-requiring patients at the early stages of chemotherapy.